OPPORTUNITIES AND PROSPECTS OF DEVELOPMENT FOR THE DIGITAL ECONOMY IN THE WORLD AND THE RUSSIAN FEDERATION - Korostelkina, Irina; Dedkova, Elena; Popova, Lyudmila; Vasilyeva, Marina; Korostelkin, Mikhail (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Implementation of digital economy tools in the new information environment is a catalyst for innovative development of the economic environment of the state as a whole. It is obvious that not all the available opportunities and resources for the development of the digital economy have found their vectors of implementation, many of them have not been studied sufficiently and haphazardly, the existing potential and prospects have not been disclosed.Understanding of the need to develop elements of the digital economy has come to a head in the Russian economic and legal environment, as evidenced by the development and implementation of priority areas of the strategy of scientific and technological development of Russia. The mentioned problems determine the relevance of the research study of the possibilities of applying the positive foreign experience of digitalization of the economy in domestic practice. The paper provides an overview of the main categories of the digital economy, examines the features of its widespread distribution in the countries of the world, assesses the opportunities and prospects for the development of digitalization in Russia. New technologies, criteria and approaches to assessing the level of the digital economy, its institutionalization require effective regulation and management.